Candide, or Pessimism: Fighting Piracy and Transnational Crime in Uncharted Waters - Tom Syring (Interdisciplinary Political Studies, 2012)
While Somali pirates have been dominating the headlines in recent years, piracy and armed robbery at sea represents a widespread phenomenon throughout the world’s most traveled waterways. Having a piracy problem in one’s “maritime backyard” exposes the inadequacy of the coastal state’s patrolling and prosecutorial capacity and adds to the incentives of criminal enterprises to operate in the area. In order to contain the threat posed by piracy, various national and international efforts at patrolling and policing the oceans, and prosecuting pirates, have been initiated—often, however, without capturing the root causes of the problem. While the UN Convention on the Law of the Sea (UNCLOS) defines specific acts of piracy, it does not include financing and other “secondary activities”, which typically create and sustain piracy networks. This article argues that regarding pirate activities through the lenses of transnational organized crime may provide a more adequate basis for addressing piracy.